EFFECT OF OUTSOLE THICKNESS ON RUNNING BIOMECHANICS - Cheng, Chan Siow; Lin, Koh Wei; Qing, Tan Yin (Malaysian Journal of Science, 2022)
Running shoes with increased or decreased sole thickness are postulated to improve running performance, besides to protect runners against high impact forces and running injuries. However, there is no evidence showing that running shoe developments emerging on the market help tackle running injuries. In this study, we compared the effect of different outsole thicknesses: (i) barefoot, (ii) minimalist and (iii) maximalist sports shoes on running biomechanics. Fifteen male subjects (age 23.19 ± 0.73 years old) who had regular exercises for at least 75 minutes per week were recruited to participate in this study. Participants had completed three minutes of running on a treadmill in each condition. Lower extremity kinetics and kinematics were analysed. There was no difference between maximalist running shoes and minimalist running shoes with respect to maximum vertical ground reaction force (VGRF) (p = 0.221), step length (p = 0.50) and cadence (p = 0.30). In addition, we observed longer ground contact time in maximalist running shoes (1.087 ± 0.115 s) when compared with minimalist running shoes (1.051 ± 0.105 s) (p = 0.007). On the other hand, runners had significantly higher knee flexion and adduction in minimalist shoes than maximalist shoes (p = 0.046). In conclusion, running in minimalist shoes, at least in a short period, produces greater running efficiency with shorter ground contact time but may result in a higher injury risk at the knee joint.